Deep subwavelength graphene-dielectric hybrid plasmonic waveguide for compact photonic integration - Xueqing He; Tigang Ning; Li Pei; Jingjing Zheng; Jing Li; Jianshuai Wang (Results in Physics, 2021)
In this paper, we propose a novel graphene-dielectric hybrid plasmonic waveguide (GDHPW). The fundamental hybrid mode characteristics guided by the GDHPW are numerically investigated. The results show ultra-small mode area (~10−4λ2) and long propagation length (tens of micrometers) can be simultaneously realized by tuning the key geometric structure parameters and the chemical potential of graphene. In addition, we also analyze the crosstalk properties about the two GDHPWs placed on a substrate and ultralow crosstalk can be achieved. Moreover, several alternative modified structures with remarkable optical confinement performances are proposed. The GDHPW with strong optical confinement is expected to serve as a fundamental building block for various tunable high-density integrated photonic components and devices.